{4-Chloro-2-[(2-hydroxyethyl)iminomethyl]phenolato}{4-chloro-2-[(2-oxidoethyl)iminomethyl]phenolato}cobalt(III) - Liu, Li-Jun (International Union of Crystallography, 2010)
In the title mononuclear cobalt(III) compound, [Co(C(9)H(8)ClNO(2))(C(9)H(9)ClNO(2))], the Co(II) atom is six-coordinated by two imine N atoms, two phenolate O atoms, and one hydroxy and one oxide O atom from two Schiff base ligands, forming an octahedral geometry. In the crystal structure, adjacent molecules are linked through intermolecular O—H⋯O hydrogen bonds. The 2-oxidoethyl group is disordered over two positions in a 0.638 (3):0.362 (3) ratio.